VARIABEL YANG MEMPENGARUHI PERILAKU PEMBELIAN GREEN PRODUCT PADA GENERASI MUDA - Wijaya, Khatleen; Soelasih, Yasintha (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2020)
Abstract: At the time environmentally friendly products produced by the company The purpose of this research is to see that the younger generation at this time already has an awareness of green products. The development of green product is expected to be protected by the existing environment. Therefore, the interaction of purchasing green product is expected to emerge in the younger generation. This research focuses on the influence of care, attitude and responsibility towards purchase behavior of green product in the younger generation. The number of samples taken was 518 respondents. Sampling was carried out for young people in the areas of Jakarta, Bogor, Depok, Tangerang and Bekasi. Sampling used  by purposive sampling included in non-probability. The instrument was tested for reliability and validity. Reliability test using Cronbach's alpha while validity used confirmatory factor analysis. Hypotheses test used structural equation modeling.  The results of the study show that hypothesis 1 is significant, while hypotheses 2 and 3 are not significant.  Keywords:    care, attitude, responsibility, purchase behavior, green product, younger generation